PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 8 PADANG - Feby Herdiana Putri (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication is one of the abilities that must be possessed by students in mathematics learning. However, in reality the mathematical communication skills of students in class VIII SMPN 8 Padang were still relatively low. Efforts to overcome these problems were by implementing learning models that could make students active and able to communicate mathematically. One of the learning models is the TTW cooperative learning model. This study aimed to determine whether the mathematical communication skills of students who apply the TTW type cooperative learning model were better than the mathematical communication skills of students who learning with conventional learning models in class VIII of SMP 8 Padang in the academic year 2018/2019. This type of research was quasi-experiment with static group design, with a population of eighth grade students of SMP 8 Padang in the academic year 2018/2019. Sampling was done by random sampling technique, students in class VIII C as the experimental class and class VIII F as the control class. The instrument used the final test in the form of essay questions to see students' mathematical communication skills. Data analysis was performed bytest Mann Whitney U-. Based on the analysis of research data atit is obtained P-value = 0.0000, because the P-value, then reject. So, it can be concluded that the mathematical communication skills of students whose learning using the TTW cooperative learning model is better than students who use conventional learning models.Keywords—Mathematical Communication ability, TTW, Cooperatif Learning.